2022-RA-1477-ESGO Neoadjuvant platinum-based dose-dense chemotherapy in patients with locally advanced cervical cancer. (20th October 2022) - Smirnova, Olga; Mamontova, Anna; Abramova, Alina; Nyuganen, Anna; Trifanov, Yuri; Ulrikh, Elena; Urmancheeva, Adel; Berlev, Igor
Abstract : Introduction/Background: To evaluate the results of dose-dense neoadjuvant chemotherapy (NACT) in treatment of locally advanced cervical cancer IB2-IIB stages. Methodology: A cohort of 120 consecutive patients with median age of 43 (range 27–68) years was studied. All patients had verified locally-advanced (cT1в2Nх, 0M0; cT2вNх, 0M0) cervical cancer and received 3 dose-dense intravenous neoadjuvant AP (cisplatin 75 mg/m2, doxorubicin 35 mg/m2; n=58) or TP (cisplatin 60 mg/m2 and paclitaxel 60 mg/m2; n=62) chemotherapy cycles. To determine prognostic factors, 2 retrospective groups of patients were examined: group I – surgical treatment without NACT (n=25; IB2 stage), group II – concomitant chemoradiotherapy (n=44; IIB stage). Results: The median follow-up was 31 months. The overall 3-year survival rates in was 94.2%. The 4-year disease-free survival rate was 87.5%. The disease-free survival rate was higher in group with NACT (p = 0.03).According to RECIST 1.1 criteria the complete response rate was 10% (12/120 cases), partial response 57.5% (69/120 cases), stable disease 29.2% (35/120 cases), progressive disease 3.3% (4/120 cases). The surgical intervention was performed in 82.5% (99/120 cases), in 17, 5% (21/120) – concomitant chemoradiotherapy. The pathomorphological response rate was 85, 8% (85/99 cases). The complete morphological tumor regression (ypCR) was confirmed in 12, 1% (12/99cases). An independent prognostic factors of the recurrence were parametric invasion and tumor degree differentiation. Conclusion: The dose-dense chemotherapy is an effective treatment modality for cervical cancer IB2-IIB stages and may be a feasible alternative for standard treatment approach.